Comparative Analysis of Blood Alcohol Concentration Thresholds and Criminal Responsibility in Indonesia and Germany - Josephine Steffanie; Ibrahim, Aji Lukman (Al-Risalah, 2026)
Criminal liability is based on the perpetrator's awareness and ability. However, Indonesian criminal law still experiences a normative gap because it does not regulate the blood alcohol concentration (BAC) limit as an objective parameter for assessing the ability to be responsible. As a result, judges' assessments are subjective and lead to disparities in decisions. This normative-comparative research aims to analyze the gap in the BAC norm in Indonesia by comparing it to the German criminal law system. The method used is normative legal research with a legislative, conceptual, and comparative approach, using literature study data. The results show that Germany sets a BAC limit of 0.3–1.09‰ for relative impairment and ≥1.1‰ for complete loss of ability, while Indonesia does not have a similar standard. The novelty of this research lies in the formulation of a concept for determining a measurable and applicable alcohol level limit in Indonesia, namely the proposed addition of Article 38A to the National Criminal Code with a BAC limit of 0.03%–0.1%. This determination is recommended to realize legal certainty, proportionality, and substantive justice in the Indonesian criminal law system.